MULTIKULTURALISME DAN PENDIDIKAN DAMAI PERSPEKTIF KH. ABDURRAHMAN WAHID - Muhammad Ulul Fahmi (Oasis : Jurnal Ilmiah Kajian Islam, 2022)
This study aims to reveal the importance of multicultural values and peace education from the perspective of KH. Abdurrahman Wahid. This study uses a qualitative approach to the type of literature review (library research). The data collection uses the documentation method, while the data analysis technique is carried out by content analysis. The analysis was carried out by examining the works of KH. Abdurrahman Wahid related to multicultural values and peace education. The results of this study indicate that the ideas of KH. Abdurrahman Wahid about multiculturalism can be used as material and reference in peace education, so that those people who are full of hatred and anger to commit various acts of violence, conflict, intolerance and radicalism eventually become peaceful, full of love, and tolerant people. It leads to a more tolerant, just, and peaceful society.